2018
DOI: 10.1016/j.clim.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Unique glandular ex-vivo Th1 and Th17 receptor motifs in Sjögren's syndrome patients using single-cell analysis

Abstract: Primary Sjögren's syndrome (pSS) is an autoimmune disease in which the underlying cause has yet to be elucidated. The main objective of this study was to determine the T cell receptor (TCR) repertoires of individual infiltrating T helper (Th)-1 and 17 cells of pSS patients using single-cell analysis. Single-cell analysis of ex-vivo infiltrating T cells demonstrated that pSS patients had higher frequencies of activated Th17 cells. Single-cell TCR sequencing revealed that TCRβ variable (TRBV)3-1/joint (J)1-2 (CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…Suggestive GSEA results that did not pass correction for multiple comparison testing showed trends toward a dearth of Th17 cells and enrichment of Tcm and activated Treg populations in SS SG biopsies. The lack of detection of a Th17 gene signature among salivary gland CD4 + T cells is consistent with a prior report finding that CD4 + T cells with IL-17 production potential occur at low frequency (<0.2%) among CD4 + T cells in SS SG tissue [46]. Our study, which sampled 200 sorted memory CD4 + T cells per subject, was designed to detect prevalent differentiation states and to ensure adequate sampling from the non-SS control group.…”
Section: Discussionsupporting
confidence: 86%
“…Suggestive GSEA results that did not pass correction for multiple comparison testing showed trends toward a dearth of Th17 cells and enrichment of Tcm and activated Treg populations in SS SG biopsies. The lack of detection of a Th17 gene signature among salivary gland CD4 + T cells is consistent with a prior report finding that CD4 + T cells with IL-17 production potential occur at low frequency (<0.2%) among CD4 + T cells in SS SG tissue [46]. Our study, which sampled 200 sorted memory CD4 + T cells per subject, was designed to detect prevalent differentiation states and to ensure adequate sampling from the non-SS control group.…”
Section: Discussionsupporting
confidence: 86%
“…reported that the TRBV3-1 gene was highly expressed in Th1 and Th17 cells of primary Sjögren's syndrome patients 48 . Further, the abnormal expression of TRBV3-1 and TRBJ2-7 might be associated with the pathogenesis of immune-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Th1 and Th17 cells have long been implicated as crucial mediators at early stages of SS pathology, contributing in shape up the inflammatory microenvironment ( Figure 1 ). Such notion was emphasized by the fact that both pSS-infiltrating activated Th1 and Th17 subsets presented restricted clonal diversities with TCR recognizing common autoantigen unique to pSS [ 27 ]. Th1 cells have also been narrowly associated to development and disease severity, owing to their selective infiltration into target tissues, analyzed by the presence of the transcription factor T-bet and IFN-γ [ 28 ].…”
Section: Th1/th17 Cells: Primordial Effectors Coordinating the Infmentioning
confidence: 99%